Learning and transfer of visual anticipation in skilled cricket batsmen - Brenton, J. (Murdoch University, 2018)
This PhD thesis investigated whether visual-perceptual training or visual-perceptual training with acquisition of the observed motor pattern was the most effective to improve visual anticipation. Experiment 1 validated a temporal occlusion video test to discriminate fine-grained differences in visual anticipation between groups of skilled cricket batsmen, which was used in testing phases of subsequent experiments. Experiment 2 recruited club cricket batsmen, who were randomised into three groups: (i) visual-perceptual training, (ii) visual-perceptual training with motor practice of the observed bowler`s action, and (iii) control group that receiving no training. Results indicated both training groups, but not the control group, significantly improved anticipation of ball types from the bowler`s action across pre-to-post-tests. However, only visual-perceptual training with acquisition of the observed bowler`s action transferred to superior anticipation against different bowlers. Findings supported common-coding theory, which predicts that visual and motor experience influence visual-perception (anticipation). To probe the contribution of motor experience, a further experiment was conducted to interfere with acquisition of the motor pattern. Results indicated that interfering with motor pattern acquisition inhibited learning and transfer of anticipation, confirming the importance of motor experience to improved anticipation. Experiment 3 applied visual-perceptual-motor pattern training to a group of emerging expert state cricket batsmen. Results indicated that the intervention group, but not the control group, significantly improved their anticipation across pre-post-transfer tests, again supporting the predictions of common-coding theory. Overall, these findings advanced theoretical knowledge of the contributions to visual and motor experience to anticipation, as well as providing practical applications for skill acquisition specialists and coaches to assist designing practice sessions to improve visual anticipation skill. Furthermore, a new instrument was developed to automatically trigger occlusion glasses that could in future be used to assess improvements in anticipation to field settings of batting.